THE RELATIONSHIP BETWEEN CHILDHOOD OBESITY AND DENTAL HEALTH. AN OBSERVATIONAL STUDY - Iuliana Margasoiu; Laura Mihaela Trandafir; Alexandra Georgeta Grigorescu; Lorena Manole; Gabriela Ghiga; Gabriela Stoleriu (Romanian Society of Oral Rehabilitation, 2024)
The prevalence of obesity among children is rising and over the years we can estimate the severity of medical issues at adult age. According to the latest studies and also personal experience we are already seeing the first signs of diabetes, high blood pressure and non-alcoholic fatty liver disease (NAFLD) in children and adolescents. The excess of sugar and refined carbohydrates associated with a sedentary lifestyle has multiple negative effects for organism and high risk of comorbidities, especially for dental health of children. We also notice problems in the dental field and here we refer to dental caries and dental demineralization. Aim of the study: In this observational study we set out to find out the possible correlation between obesity in children and dental problems by evaluating the body mass index, percentile, and a self-assessment method for dental problems using the ADA's Caries Risk Assessment. Materials and Methods: In this study 51 children with ages between 7 and 17 years old were evaluated in the nutrition office. The degree of obesity was established using the body mass index and percentile. Each participant then had to fill out and ADA's Caries Risk Assessment form for patients over 6 years of age. Results: Out of the 42 children with obesity or overweight that completed ADA's Caries Risk Assessment form, 50% associate dental problems, more precisely carious lesions, according to the answers received using the ADA form, the high prevalence is correlated with sugar consumption. Conclusions: The analysis of the study lot highlighted a significant correlation between weight and oral health, which means that a poor diet, rich in refined sugars, may lead to obesity and also dental lesions. Improving collaboration between general and oral health professionals is essential to improve health and also to prevent the development of more serious comorbidities.